Campaign fund-raising abuses and money laundering in recent U.S. elections: criminal networks in action - Liddick, Don (Crime, law and social change, 2000)
This study describes some of the campaign fundraising abuses perpetuated by Republican and Democratic operatives in connection with recent U.S. elections. Efforts to conceal the source of campaign contributions or to evade contribution and spending limits involved a variety of money laundering techniques including the use of shell companies, straw donors, and the funnelling of money through political action committees and non profit tax-exempt organizations. In addition to the brazen sale of political access, some of the more serious infractions involved the infusion of foreign money into the Republican and Democratic National Committees as well as the Clinton-Gore reelection campaign. The author concludes the crimes that were committed are explained best as organized criminality manifested as complex networks of patron-client relationships.